Potential contribution of early endothelial progenitor cell (eEPC)-to-macrophage switching in the development of pulmonary plexogenic lesion - Feng-Jin Shao; Xiao-Ling Guo; Jia-Xue Xu; Rui Liu; Dan-Yue Li; Qing-Hao Li; Ting Zhou; Cun Fang; Xun Tan (Respiratory Research, 2022)
Abstract Background Plexiform lesions, which have a dynamic appearance in structure and cellular composition, are the histological hallmark of severe pulmonary arterial hypertension in humans. The pathogenesis of the lesion development remains largely unknown, although it may be related to local inflammation and dysfunction in early progenitor endothelial cells (eEPCs). We tested the hypothesis that eEPCs contribute to the development of plexiform lesions by differentiating into macrophages in the setting of chronic inflammation. Methods The eEPC markers CD133 and VEGFR-2, macrophage lineage marker mannose receptor C-type 1 (MRC1), TNFα and nuclear factor erythroid 2-related factor 2 (Nrf2) in plexiform lesions in a broiler model were determined by immunohistochemistry. eEPCs derived from peripheral blood mononuclear cells were exposed to TNFα, and macrophage differentiation and angiogenic capacity of the cells were evaluated by phagocytotic and Matrigel plug assays, respectively. The role of Nrf2 in eEPC-to-macrophage transition as well as in MRC1 expression was also evaluated. Intratracheal installation of TNFα was conducted to determine the effect of local inflammation on the formation of plexiform lesions. Results Cells composed of the early lesions have a typical eEPC phenotype whereas those in more mature lesions display molecular and morphological characteristics of macrophages. Increased TNFα production in plexiform lesions was observed with lesion progression. In vitro studies showed that chronic TNFα challenge directed eEPCs to macrophage differentiation accompanied by hyperactivation of Nrf2, a stress-responsive transcription factor. Nrf2 activation (Keap1 knockdown) caused a marked downregulation in CD133 but upregulation in MRC1 mRNA. Dual luciferase reporter assay demonstrated that Nrf2 binds to the promoter of MRC1 to trigger its expression. In good agreement with the in vitro observation, TNFα exposure induced macrophage differentiation of eEPCs in Matrigel plugs, resulting in reduced neovascularization of the plugs. Intratracheal installation of TNFα resulted in a significant increase in plexiform lesion density. Conclusions This work provides evidence suggesting that macrophage differentiation of eEPCs resulting from chronic inflammatory stimulation contributes to the development of plexiform lesions. Given the key role of Nrf2 in the phenotypic switching of eEPCs to macrophages, targeting this molecular might be beneficial for intervention of plexiform lesions.